EFEKTIVITAS MEDIA SOSIAL DALAM MENGOMUNIKASIKAN ASPIRASI MASYARAKAT UNTUK PERBAIKAN KINERJA DAN PEMBANGUNAN BERKELANJUTAN - Laksana, Putu Ari Satya; Asmara Yanti, Ni Nyoman Suli (IAHN Gde Pudja Mataram, 2023)
This study aims to determine the effectiveness of using social media in communicating community aspirations for performance improvement and sustainable development. This research looks at the phenomenon of the widespread use of social media, especially the making of short videos by content creators on social media to convey aspirations regarding the surrounding conditions that need to be addressed by the parties responsible for this matter. The use of social media that is currently being used is the social media Tiktok. This research method uses a descriptive analysis of the phenomena that occur according to the results of observations and data extraction from 150 samples of netizen comments taken on viral Tiktok video uploads. The results of this study indicate that the use of social media as a forum for conveying aspirations is considered effective as evidenced by the responses given both by the public and from the authorities. The transformation of the increasingly massive use of social media can facilitate people in conveying their aspirations easily without being hindered by distance and time. Social media can help the public to get answers and responses from the authorities in terms of following up on the aspirations conveyed. In addition to responses, follow-up is also given to resolve problems in order to improve performance and sustainable development. A good sustainable developer will have an impact on improving the economy and increasing regional income. Increasing economic conditions will have an impact on people's welfare and people's lives which are expected to be more advanced than before.